(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mushrooms have high protein content, usually around 20-30% by dry weight. This can be useful for vegetarians or anyone looking to increase the protein content in their diet. Pleurotus mushrooms commonly known as oyster mushrooms grow in the wild in tropical, subtropical and temperate regions. Cultivation of Pleurotus is a valuable and profitable agribusiness and is gaining rapid popularity amongst the entrepreneurs. In the present study quantitative phytochemical analysis of edible mushroom Pleurotus opuntiae was analysed using the extract acetone, aqueous and petroleum ether in the substrates of paddy straw and jack leaves The compounds such as protein and amino acid, glycoside, flavonoid, phenol and tannin were analysed. Antioxidant activity was determined by Superoxide anion scavenging activity, Hydroxyl radical scavenging assay and DPPH radical scavenging activity using the solvent acetone.